Prophylactic Chemotherapy for the Prevention of Gestational Trophoblastic Neoplasia- A descriptive study - Ayesha Saif, Nabeela Shami, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gestational trophoblastic neoplasia develops from the trophoblastic cells which later form the placenta. It ranges from the relatively benign partial and complete hydatidiform mole while choriocarcinoma and the rare placental site trophoblastic tumor are its malignant variants. The risk of developing gestational trophoblastic neoplasia (GTN) is 15-17% after complete mole and 3.5-4% after partial mole1,2. This risk is more in patients with high-risk molar pregnancy1,2. Aim: To evaluate the role of prophylactic chemotherapy in prevention of gestational trophoblastic neoplasia in patients who fall in high-risk molar category. Place and duration of study: Ghurki Trust Teaching Hospital and Surgimed Hospital, 2016-2020 (4 years duration) Study design: Descriptive case series Methodology: Twenty three patients who presented with high-risk molar pregnancy in the study period were included in this study after takinginformed consent.These patients were divided into two groups. Group A included those patients who underwent suction evacuation followed by prophylactic chemotherapy; they were 13 in number, while group B had 10 patients and they underwent suction and evacuation only. Single dose of methotrexate 1mg/kg body weight was given to the patients in group A. Patients were asked about the history of excessive vaginal bleeding and serial beta hcg levels were carried out on follow up. Results: The patients average age was 32 years with the range between 25-42 years.14 patients (61%) were more than 40 years old while 9 patients (39%) were less than 40 years old. Three patients had beta hcg levels above 100,000 IU/ml. Patients were followed up withserial beta hcg levels till they became negative.No patient (0%) in group A developed gestational trophoblastic neoplasia while two patients (15.3%) in group B developed persistent vaginal bleeding and 1 patient (7%) developed choriocarcinoma involving the brain. Conclusion: Prophylactic chemotherapy reduces the risk of development of gestational trophoblastic neoplasia as concluded by thisstudy. However, only 16% of patients in high-risk molar category develop gestational trophoblastic neoplasia2 which means this will expose 84% patients to unnecessary chemotherapy. This will increase the cost of treatment also. Keywords: Molar pregnancy, Prophylactic chemotherapy, Gestational trophoblastic neoplasia